A Comparative Study of the Effect of Using RO Water on Zinc and Copper Level and its Effect on the Level of Hemoglobin in Pregnant Women - Wally, Riyadh Hussein (Al-Nahrain Journal of Science, 2018)
This study was conducted in the department of pathological analysis in Al-Kut technical institute of Iraq, were the total dissolved solid (TDS) and the level of zinc and copper trace elements measured for tap water and reverse osmosis RO water in several areas of Al-Kut city. Two groups of healthy pregnant women attending maternity health centers in Al-Kut city were selected for this study during the week 24-28 of gestation, aged between 20-40 years. The first group consisted of 55 pregnant women using tap water as drinking source and the second group also included 55 pregnant women using RO water as drinking source. The blood samples were collected from both groups and hemoglobin, zinc and copper levels were measured in both groups. The study showed a highly decreased in the level of TDS(15 + 5), zinc (1 + 0. 1) and copper (1 + 0. 2) of RO water in comparison with tap water were TDS(680 + 32), zinc (5.4 + 2.1) and copper (8.7 + 3.1) also study show significance decrease in hemoglobin(10.8 + 1.1), zinc(7.8 + 1.8) and copper (9.1 + 2.1) levels in pregnant woman who drinking RO water in comparison with woman drinking tap water were the level of hemoglobin(11.3 + 1.3), zinc(9.4 + 2.6) and copper(10.9 + 3.6).